1982
DOI: 10.1107/s0567740882005093
|View full text |Cite
|
Sign up to set email alerts
|

The room-temperature structure of BaZnGeO4

Abstract: The room-temperature phase of BaZnGeO4 shows two types of superlattice reflexions. The first appear on the (001)* reciprocal-lattice plane, giving relationships a = asu b --bsu b and b = asu b + 2bsu b. The second type appear along the e* direction, and are very weak and incommensurate with a relationship e _~ 4esu b. The superstructure has been determined neglecting the incommensurate reflexions. The space group is P63 with unit-cell dimensions a = 9.2905 (3), c = 8.728 (1) A and Z = 6. The final R is 0.0464 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Diffraction powder data about the BaZnSiO 4 structure were reported in JCPDS-International Centre for Diffraction 11 in agreement with Do Dinh and Durif . However, other studies established the existence of a (2 × A , C ) superstructure for BaAl 2 O 4 and a temperature-dependent ( × A , 4 × C ) superstructure for BaZnGeO 4 . BaMgSiO 4 and BaZnSiO 4 compounds were also reinvestigated using powder X-ray and neutron diffractions, and the discovering of a new isostructural compound, BaCoSiO 4 , was reported by Liu and Barbier . Those authors refined the crystal structures of BaMSiO 4 (M = Co, Mg, and Zn) compounds and showed that they are isostructural Ba-stuffed derivatives of tridymite (SiO 2 ) and crystallize with a ( × A , C ) superstructure of hexagonal ( A , C ) kalsilite (KAlSiO 4 ).…”
Section: Resultsmentioning
confidence: 61%
“…Diffraction powder data about the BaZnSiO 4 structure were reported in JCPDS-International Centre for Diffraction 11 in agreement with Do Dinh and Durif . However, other studies established the existence of a (2 × A , C ) superstructure for BaAl 2 O 4 and a temperature-dependent ( × A , 4 × C ) superstructure for BaZnGeO 4 . BaMgSiO 4 and BaZnSiO 4 compounds were also reinvestigated using powder X-ray and neutron diffractions, and the discovering of a new isostructural compound, BaCoSiO 4 , was reported by Liu and Barbier . Those authors refined the crystal structures of BaMSiO 4 (M = Co, Mg, and Zn) compounds and showed that they are isostructural Ba-stuffed derivatives of tridymite (SiO 2 ) and crystallize with a ( × A , C ) superstructure of hexagonal ( A , C ) kalsilite (KAlSiO 4 ).…”
Section: Resultsmentioning
confidence: 61%
“…These compounds crystallize in hexagonal unit cells, suggesting that they are isostructural with kalsilite (KAlSiO 4 ). However, a (2 × A,C) superstructure for BaAl 2 O 4 , and a temperature‐dependent ( 3 × A, 4 × C) superstructure for BaZnGeO 4 have also been reported . Powder X‐ray diffraction (XRD) and neutron diffraction studies have been used to reinvestigate the crystal structure of BaMgSiO 4 and BaZnSiO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…BZGO:Bi 3+ crystallizes in the hexagonal system with a stuffed structure derived from the high-tridymite framework. 17 BZGO and a = b = 9.301 Å, c = 8.825 Å, and V = 661.216 Å 3 for BZGO:0.6%Bi 3+ . Crystal structure of BZGO is shown in Figure 1D, and the coordination environments of Ba 2+ , Zn 2+ and Ge 4+ ions are depicted in the insets of Figure 1B,C.…”
Section: Phase Identification and Crystal Structurementioning
confidence: 96%
“…Three Ba 2+ sites are all surrounded by nine oxygen atoms, as depicted in Figure 1B, and Ba 2+ ions are on the midplane of the two neighboring layers. 17 As for the site occupancy, the ionic radium of Bi 3+ (1.03 Å) is similar to that of Ba 2+ (1.35 Å), and far larger than that of Zn 2+ (0.74 Å) and Ge 4+ (0.53 Å) with the same coordination number 18 ; thus the doped Bi 3+ ions are considered to occupy Ba 2+ sites in BZGO:Bi 3+ .…”
Section: Phase Identification and Crystal Structurementioning
confidence: 96%
See 1 more Smart Citation